2008
DOI: 10.1111/j.1365-3164.2008.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of superficial suppurative necrolytic dermatitis of miniature schnauzers with identification of a causative agent using patch testing

Abstract: A 9-year-old, castrated male, miniature schnauzer presented with malaise, anorexia, fever and severe inflammatory skin lesions on the dorsum, thighs and pinnae. The lesions developed 2 days after bathing with a commercial shampoo. Histopathological examination of skin samples revealed neutrophilic exocytosis, parakeratosis, epidermal hyperplasia and neutrophilic infiltration in the superficial dermis. Skin lesions resolved completely after 14 days of treatment with prednisolone and ofloxacin. Patch testing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Dogs may have concurrent systemic signs including pyrexia or lethargy. Scott et al reported 2 cases of SSND of 101 dogs with adverse drug reactions, and Murayama et al confirmed shampoo as an etiologic agent of SSND by patch testing in a Miniature Schnauzer …”
Section: Common Clinical Patterns Associated With Drug Allergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs may have concurrent systemic signs including pyrexia or lethargy. Scott et al reported 2 cases of SSND of 101 dogs with adverse drug reactions, and Murayama et al confirmed shampoo as an etiologic agent of SSND by patch testing in a Miniature Schnauzer …”
Section: Common Clinical Patterns Associated With Drug Allergiesmentioning
confidence: 99%
“…Skin testing (prick testing, patch testing, or intradermal testing) has been used in human patients to diagnose various allergic responses in sensitized patients . There are a limited number of reports of patch testing being performed in veterinary medicine . Prick testing and intradermal testing are used to evaluate immediate reactions caused by IgE allergic reaction, and are evaluated within 24 hours, whereas for delayed reactions both intradermal testing (IDT) or patch testing are options, and require readings up to 72 hours.…”
Section: How To Recognize and Diagnose Adrmentioning
confidence: 99%
“…In contrast, in veterinary medicine, there are only few reports about the use of skin tests as diagnostic tools for ADRs. In 2008, Murayama described PT to identify an allergic reaction to ingredients of a shampoo in a miniature schnauzer ( 20 , 45 ). Apart from this, PT proved useful as an aid to choose the ingredients of an elimination diet in dogs with adverse food reaction ( 27 ), and IDT is widely used to identify offending environmental allergens in dogs with atopic dermatitis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology is unknown; however, a cutaneous adverse drug reaction, or exposure to allergens or a b immunogens in shampoos is suspected. [1][2][3][4] Diagnosis is based on clinical findings, histopathological features and the history of known chemical exposure. A long-acting (eight month), rapid onset flea and tick collar containing 10% imidacloprid and 4.5% flumethrin in a matrix polymer (Seresto, Bayer HealthCare LLC; Shawnee Mission, KS, USA) slowly and continuously releases active ingredients from the site of contact and disperses over the entire skin surface according to a concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs typically develop within 48–72 h postapplication of product. The aetiology is unknown; however, a cutaneous adverse drug reaction, or exposure to allergens or immunogens in shampoos is suspected 1‐4 . Diagnosis is based on clinical findings, histopathological features and the history of known chemical exposure.…”
Section: Introductionmentioning
confidence: 99%